Solution Method of Common Constraint of the Mechanism in the Modified G-K's Formula - Xu Zhaotang (Jixie chuandong)
In the calculation of mobility of the mechanism using the modified Grübler-Kutzbach's formula of mechanism mobility, the common constraint of the mechanism has to be solved. In order to obtain the common constraint of the mechanism with a simpler method and on the basis of defining the common constraint of the mechanism, the coordinate direction of the mechanism without common constraint is obtained according to the mobility of kinematic pair and the constraint direction of the kinematic pair whose absolute motion is not zero, and then the common constraint of the mechanism is determined in other coordinate direction. The total number of coordinate directions with and without the common constraint of the mechanism is 6. The common constraint of the mechanism is equal to the number of coordinate directions with common constraint. This method does not need the screw theory to solve the common constraints of the mechanism, which is convenient for engineering and technical personnel to solve the common constraints of the mechanism. It is also convenient for the modified Grübler-Kutzbach's formula of the mechanism mobility to be popularized and applied in engineering and technical personnel.